INFORMATION TECHNOLOGIES IN TRAINING - Gerbekov, H.A.; Baychorova, S.K.; Laypanova, M.S. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2017)
In the modern society one of the main competences of the person is ability quickly and qualitatively to work with information technologies to create and adapt to the tasks electronic resources with use of the modern information technologies. Thus the educational task of formation information competence and the level of information culture conforming to requirements of the modern information society is urgent. Significantly the role of a subject of the information scientist increases in school in connection with increase in a role of process of informatization of society in general and education informatization in particular. Priorities in the maintenance of school course of informatics are redistributed. One of key roles in school course of informatics is played by the “Information technologies” line.In the article is carried out the short review of primary partitions of the informative line “Information technologies” of school course of informatics. The hardware of information technologies, the software of information technologies and means of telecommunications concern them. In article the short analysis of the basic concept on each of these sections is carried out. Besides some methodical recommendations about training in these sections are provided. It is reasonable that elements of fundamental education shall is aware informatics in any technological subject to find the place.